PENGGUNAAN MEDIA FLASHCARDS UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR PESERTA DIDIK SEKOLAH DASAR - Cicik Harirah Yuliastuti; Meirza Nanda Faradita; Iswahyuni (Universitas Muhammadiyah Surabaya, 2024)
This research aims to determine the increase in student activeness and learning outcomes in Pancasila Education lessons on Cultural Diversity material through flashcards media. This type of research is Classroom Action Research (PTK). The research subjects were 4th grade students of Taquma Surabaya Elementary School totaling 26 students. Data collection techniques using technical tests in the form of evaluation questions and non-tests in the form of observation. This research was conducted with two cycles. The results showed that in cycle 1 many students were not complete with only 60% completeness, in cycle 2 the completeness increased by 90% or 23 students and 10% or 3 students were not complete. As for the liveliness assessment in cycle 1, the liveliness of presentations and discussions is still lacking but has been improved in cycle 2 with the results that have developed as expected is 58% or 15 students where there is an increase of 6 students. , and those that have been cultured from a percentage of 35% or 9 students have increased by 14% or 11 students who have begun to be cultured. Thus proving that flashcards media can improve learning outcomes and student activeness in Pancasila Education lessons on Cultural Diversity material.